(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the linguistic and structural features of lexical units used in the field of entrepreneurship. It analyzes the mechanisms of word formation, semantic shifts, stylistic tendencies, and borrowing processes. The study also highlights how global business trends and technological innovation have contributed to the development of a distinct entrepreneurial lexicon.